BioSAXS at European Synchrotron Radiation Facility – Extremely Brilliant Source: BM29 with an upgraded source, detector, robot, sample environment, data collection and analysis software. (16th December 2022) - Tully, Mark D.; Kieffer, Jerome; Brennich, Martha E.; Cohen Aberdam, Raphael; Florial, Jean Baptiste; Hutin, Stephanie; Oscarsson, Markus; Beteva, Antonia; Popov, Anton; Moussaoui, Dihia; Theveneau, Pascal; Papp, Gergely; et al.
Abstract : As part of its Extremely Brilliant Source (EBS) upgrade project, the ESRF's BioSAXS BM29 beamline was subject to a significant upgrade. Its bending magnet source was replaced by a two‐pole wiggler, and a larger hybrid‐pixel detector, a new sample changer and improved sample exposure cells were also installed and commissioned. Additionally, nearly all beamline software, including that for experiment control and data analysis, was renewed. Here the current status of the beamline is described, including new opportunities post‐ESRF–EBS. Abstract : As part of its Extremely Brilliant Source (EBS) upgrade project, the ESRF's BM29 BioSAXS beamline was subject to a significant upgrade and refurbishment. In addition to the replacement of the beamline's original bending magnet source by a two‐pole wiggler, leading to an increase in brilliance by a factor of 60, the sample environment of the beamline was almost completely refurbished: a vacuum‐compatible Pilatus3 X 2M with a sensitive area of 253.7 mm × 288 mm and frame rates up to 250 Hz was installed, increasing the active area available and thus the q ‐scaling of scattering images taken; the sample changer was replaced with an upgraded version, allowing more space for customizable sample environments and the installation of two new sample exposure units; the software associated with the beamline was also renewed. In addition, the layout and functionality of the BSXCuBE3 ( BioSAXS Customized Beamline Environment ) data acquisition software was redesigned, providing an intuitive `user first' approach for inexperienced users, while at the same time maintaining more powerful options for experienced users and beamline staff. Additional features of BSXCuBE3 are queuing of samples; either consecutive sample changer and/or SEC‐SAXS (size‐exclusion chromatography small‐angle X‐ray scattering) experiments, including column equilibration were also implemented. Automatic data processing and analysis are now managed via Dahu, an online server with upstream data reduction, data scaling and azimuthal integration built around PyFAI ( Python Fast Azimuthal Integration ), and data analysis performed using the open source FreeSAS . The results of this automated data analysis pipeline are displayed in ISPyB/ExiSAXS . The upgraded BM29 has been in operation since the post‐EBS restart in September 2020, and here a full description of its new hardware and software characteristics together with examples of data obtained are provided.